Pengaruh Antara Self-Regulated Learning dan Flow Akademik terhadap Prestasi Akademik Mahasiswa Fakultas Teknik Universitas Muhammadiyah Gresik - Wahda Fatwalino; Asri Rejeki; Noer Suci Endah Puspitaningrum (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
This study aims to identify the influence of self-regulated learning and academic flow on the academic achievement of students of the Faculty of Engineering, University of Muhammadiyah Gresik. Academic achievement is measured through the Cumulative Grade Point Average (GPA) as an indicator of success. Internal factors such as self-regulation in learning and full involvement in academic activities are considered to play an important role in the achievement of academic achievement. Using a quantitative approach, this study involved 840 active students from various study programs at the Faculty of Engineering. Data was collected through questionnaires that measured aspects of metacognition, motivation, behavior, absorption, enjoyment, and intrinsic motivation. The results of the analysis show that self-regulated learning and academic flow contribute significantly to student academic achievement, with academic flow having a greater influence.